Biomass for dual-fuel syngas diesel power plants. Part I: The effect of preheating on characteristics of the syngas gasification of municipal solid waste and wood pellets - Prayudi Suparmin; Roswati Nurhasanah; Hendri Hendri; Muhammad Ridwan (Arab Journal of Basic and Applied Sciences, 2023)
AbstractIndonesia has the potential to develop biomass, such as MSW and wood pellets, as a source of energy. Syngas from biomass gasification can be used as fuel for dual-fuel diesel engines in order to transition energy. We investigated the gasification of MSW and wood pellets using a downdraft reactor with a capacity of 130–144 kg in order to determine the properties of the produced syngas for use in dual-fuel syngas diesel engines. Four days are dedicated to the process of preheating biomass with sunlight. The experiment was designed with an equivalent ratio of 0.22 and an oxidation zone temperature between 700 and 900 degrees Celsius. According to the experimental results, the average lower heating value of syngas produced by the air gasification of MSW biomass was 5.85 MJ/Nm3, the cold gas efficiency was 56.6%, and the carbon conversion efficiency was 94.77%. The average lower heating value from wood pellet biomass air gasification was 5.95 MJ/Nm3, the cold gas efficiency was 67.7%, and the carbon conversion efficiency was 94.28%. Solar heating of biomass has been shown to increase the calorific value of biomass gasification to syngas.